PENCEGAHAN GASTRITIS PADA REMAJA DI DESA TIBAYAN - Supardi, Supardi; Ambar Winarti; Rani Larasati (Bajang Institute, 2024)
Background : Gastritis is a condition of the gastric mucosa caused by irritation or often called ulcer disease. The common cause of gastritis is due to poor behavior, namely from lifestyle (smoking, alcohol) and irregular diet and stress management. Objective : The purpose of this study is to find out the Overview of Gasrtitis Prevention Behavior in Tibayan Village Research Method : The type of research used is quantitative descriptive. The sample used was teenagers in Tibayan Village which amounted to 83 respondents. The sampling technique used is puposive sampling. The instrument used was a questionnaire Results and Discussion: The results of the study were obtained that the average respondent was 15.45 years old, the majority of females were 63 respondents (75.9%), most of the current education is high school/vocational school as many as 48 respondents (57.8%), the behavior of preventing gastritis in adolescents in Tibayan village is to have sufficient behavior as many as 67 respondents (80.7%), good behavior as many as 8 respondents (9.6%) and poor behavior as many as 8 respondents (9.6%).